2014
DOI: 10.1103/physrevd.89.123508
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dark energy perturbations on the growth index

Abstract: We show that in clustering dark energy models the growth index of linear matter perturbations, γ, can be much lower than in ΛCDM or smooth quintessence models and presents a strong variation with redshift. We find that the impact of dark energy perturbations on γ is enhanced if the dark energy equation of state has a large and rapid decay at low redshift. We study four different models with these features and show that we may have 0.33 < γ (z) < 0.48 at 0 < z < 3. We also show that the constant γ parametrizati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 35 publications
2
35
0
Order By: Relevance
“…Therefore, we see that the asymptotic value of growth index γ ∞ of this model is somewhat smaller than that of the ΛCDM model by approximately 3%. This is expected as the agglomerations of DE perturbations usually lowers the value of the growth index [51]. It has been also observed that a redshift dependent parametrization of γ can provide a more accurate fit for the growth rate of matter clustering in comparison to a constant parametrization.…”
Section: Constant Growth Indexmentioning
confidence: 88%
“…Therefore, we see that the asymptotic value of growth index γ ∞ of this model is somewhat smaller than that of the ΛCDM model by approximately 3%. This is expected as the agglomerations of DE perturbations usually lowers the value of the growth index [51]. It has been also observed that a redshift dependent parametrization of γ can provide a more accurate fit for the growth rate of matter clustering in comparison to a constant parametrization.…”
Section: Constant Growth Indexmentioning
confidence: 88%
“…Moreover, the growth of cosmic structures are also affected by perturbations of DE when we deal with dynamical DE models with time varying EoS parameter w 1 de ¹ - (Erickson et al 2002;Bean & Doré 2004;Hu & Scranton 2004;Basilakos & Voglis 2007;Mota et al 2007;Ballesteros & Riotto 2008;Basilakos et al 2009aBasilakos et al , 2010Gannouji et al 2010;Sapone & Majerotto 2012;Batista & Pace 2013;Dossett & Ishak 2013;Basse et al 2014;Batista 2014;Nesseris & Sapone 2015;Pace et al 2014aPace et al , 2014bBasilakos 2015;Mehrabi et al 2015aMehrabi et al , 2015bMehrabi et al , 2015cMalekjani et al 2015Malekjani et al , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there are efforts towards investigating the linear growth of matter perturbations in the context of CLDE (Bean & Dore 2004;Ballesteros & Riotto 2008;Sapone & Kunz 2009;Sapone & Majerotto 2012;Batista & Pace 2013;Dosset & Ishak 2013;Batista 2014;Steigerwald, Bel & Marinoni 2014;Pace, Batista & Del Popolo 2014;Basse et al 2014). From the observational viewpoint, although it is difficult to measure the DE perturbations, it has been found that the homogeneous DE scenario fails to reproduce the observed concentration parameter of the massive galaxy clusters (Basilakos, Sanchez & Perivolaropoulos 2009).…”
Section: Introductionmentioning
confidence: 99%